2010
DOI: 10.1007/s00894-010-0905-3
|View full text |Cite
|
Sign up to set email alerts
|

Geometries of stacking interactions between phenanthroline ligands in crystal structures of square-planar metal complexes

Abstract: Stacking interactions of phenanthroline square-planar complexes in crystal structures were studied by analyzing data from the Cambridge Structural Database. In most of the crystal structures, two phenanthroline complexes were oriented "head to tail." Phenanthroline complexes show a wide range of overlap geometries in stacking interactions, while short metal-metal distances were not observed. Stacking chains with alternating overlaps were the predominant type of packing in the crystal structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…We note that the measured interplanar distances between bpy and phen ligands fall within the range 3.3−3.76 Å, which is near the center of the distribution of known interplanar distances in bpy and phen metal complexes. 29,30 The packing motif of a structure is assigned as horizontal if only face-to-face interactions are present, zigzag if both face-to-face and parallel displaced stacking interactions are present, and diagonal if only parallel displaced stacking interactions are present. A general schematic of the horizontal, zigzag, and diagonal packing motifs is shown in Figure S1.…”
Section: ■ Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We note that the measured interplanar distances between bpy and phen ligands fall within the range 3.3−3.76 Å, which is near the center of the distribution of known interplanar distances in bpy and phen metal complexes. 29,30 The packing motif of a structure is assigned as horizontal if only face-to-face interactions are present, zigzag if both face-to-face and parallel displaced stacking interactions are present, and diagonal if only parallel displaced stacking interactions are present. A general schematic of the horizontal, zigzag, and diagonal packing motifs is shown in Figure S1.…”
Section: ■ Methodsmentioning
confidence: 99%
“…For bpy ligands, however, the weaker stacking interaction allows for other interactions in the structure to direct the packing landscape and can more easily bring the stacking geometry into a nonparallel configuration that can lead to broken local inversion symmetry. 29,30 While the presence of nonparallel stacking between chiral Cu(L) 2 (H 2 O) 2+ (L = bpy, phen) complexes does not guarantee inversion symmetry breaking, nonparallel stacking reduces the number of possible configurations that lead to inversion symmetry. Local inversion symmetry is broken in the three known Cu(L) 2 (H 2 O) 2+ (L = bpy, phen) structures where nonparallel interactions are present between nearest neighbors, although the second-nearest neighbors are related by inversion in the VIKDOJ and EQIQOL structures.…”
Section: ■ Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mono- and polydentate ligands in complexes of d 8 transition metals based on N-heterocyclic aromatics have attracted considerable attention in supramolecular chemistry. 58 Owing to their preorganized square-planar geometry favoring stacking, 59,60 they are prone to undergo supramolecular polymerization, gaining further stabilization by metal–metal and/or hydrogen bonding interactions. 61,62 In addition, the intriguing photophysical properties of these molecules provide access to various applications, such as in optoelectronics or sensing.…”
Section: Introductionmentioning
confidence: 99%
“…Noncovalent interactions of aromatic systems, including parallel stacking interactions, have been extensively studied in recent years. Stacking interactions are generally studied between aromatic organic molecules or fragments; however, it was shown that other planar molecules and fragments can also be involved in stacking interactions (García et al, 2008;Carroll et al, 2008;Ostojić et al, 2008;Janjić, Petrović, Ninković & Zarić, 2011;Mukhopadhyay et al, 2004;Mosae et al, 2009;Mitchell et al, 1994;Wang et al, 2008;Tomić et al, 2006;Sredojević et al, 2007Sredojević et al, , 2010Sredojević et al, , 2012Tomić et al, 2004;Grimme, 2008;. Water molecules can form parallel alignment interactions with aromatic rings (Ostojić et al, 2008;Janjić, Veljković & Zarić, 2011).…”
Section: Introductionmentioning
confidence: 99%